Difference between revisions of "2023 AIME II Problems/Problem 4"
(Created page with "==Solution 1== We first subtract the 2nd equation from the first, noting that they both equal <math>60</math>. <cmath>xy+4z-yz-4x=0</cmath> <cmath>4(z-x)-y(z-x)=0</cmath> <...") |
(No difference)
|
Revision as of 15:35, 16 February 2023
Solution 1
We first subtract the 2nd equation from the first, noting that they both equal .
Case 1: Let
The first and third equations simplify to:
From which it is apparent that and
are solutions.
Case 2: Let
The first and third equations simplify to:
We subtract the following equations, yielding:
We thus have and
, substituting in
and solving yields
and
Then, we just add the squares of the solutions (make sure not to double count the 4), and get:
~SAHANWIJETUNGA